2018
DOI: 10.1002/anie.201808609
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Affinity‐Triggered Variations on the Optical and Electrical Properties of Dye Molecules Enabling Highly Efficient Dye‐Sensitized Solar Cells

Abstract: The synthesis, characterization, and photovoltaic performance of a series of indacenodithiophene (IDT)-based D-π-A organic dyes with varying electron-accepting units is presented. By control of the electron affinity, perfectly matching energy levels were achieved with a copper(I/II)-based redox electrolyte, reaching a high open-circuit voltage (>1.1 V) while harvesting a large fraction of solar photons at the same time. Besides achieving high power conversion efficiencies (PCEs) for dye-sensitized solar cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…Furthermore, the device exhibited high stability for low-power applications [ 71 ]. Subsequently, various research groups have studied DSSCs for different dyes such as N719 [ 72 ], N3 [ 73 ], CW10 [ 74 ], Y1A1 [ 75 ], D205 [ 72 ], Y123 [ 72 ], TF-tBu-C3F7 [ 76 ], TY6 [ 31 ], SK6 [ 74 ], SK7 [ 77 ], D35:XY1 [ 21 ], XY1b:Y123 [ 78 ], L350 [ 79 ], MD5 [ 80 ], MD7 [ 80 ], MM-6/MM-3 [ 81 ], LI-130 [ 82 ], SK6+CW10 [ 74 ], and XY1 [ 83 ] for indoor applications. The chemical structures of some dyes are depicted in Figure 6 .…”
Section: Pv Cells For Indoor Applicationsmentioning
confidence: 99%
“…Furthermore, the device exhibited high stability for low-power applications [ 71 ]. Subsequently, various research groups have studied DSSCs for different dyes such as N719 [ 72 ], N3 [ 73 ], CW10 [ 74 ], Y1A1 [ 75 ], D205 [ 72 ], Y123 [ 72 ], TF-tBu-C3F7 [ 76 ], TY6 [ 31 ], SK6 [ 74 ], SK7 [ 77 ], D35:XY1 [ 21 ], XY1b:Y123 [ 78 ], L350 [ 79 ], MD5 [ 80 ], MD7 [ 80 ], MM-6/MM-3 [ 81 ], LI-130 [ 82 ], SK6+CW10 [ 74 ], and XY1 [ 83 ] for indoor applications. The chemical structures of some dyes are depicted in Figure 6 .…”
Section: Pv Cells For Indoor Applicationsmentioning
confidence: 99%
“…Moreover, these Cu II/I bipyridyl or phenanthroline complexes exhibit very low reorganization energies to allow the regeneration of sensitizers to proceed rapidly at low driving force . However, the moderate value of short‐circuit current densities ( J SC ) in copper‐based DSSCs becomes the bottleneck for further PCE improvement . Indeed, the current lack of sensitizers with extended long‐wavelength response prevents the full potential of the copper redox shuttles from being exploited.…”
Section: Figurementioning
confidence: 99%
“…There have already been attempts to employ benzothiadiazole (BT) or quinoxaline as the auxiliary acceptors to widen the spectral response of sensitizers for copper‐based DSSCs. However, these dyes have not delivered the desired J SC increase …”
Section: Figurementioning
confidence: 99%
“…Dye‐sensitized solar cells (DSCs), which were pioneered by O'Regan and Grätzel, are considered to be one of the most promising photovoltaic (PV) technologies that have attracted intense research interest owing to their demonstrated high power‐conversion efficiency (PCE), low cost, easy fabrication, lower pollution, outstanding performance under indoor conditions with low‐intensity light, and greater flexibility than that of conventional crystalline silicon‐based solar cells . Much effort has been invested in materials development and device engineering to improve the performance of devices up to 14 % …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Much effort has been invested in materials develop-ment and device engineering to improve the performance of devicesu pt o14%. [1,[8][9][10][11][12] DSCs are composed of aw ide-band-gap semiconductor (mostly TiO 2 )d eposited on at ransparent conducting substrate, as ensitizer,a nd ar edox electrolyte. The performance of these cells is intrinsically regulated by light absorption and multichannel charge-transfer dynamics, which are mainly dominated by sensitizers.…”
Section: Introductionmentioning
confidence: 99%